In vitro evidence suggesting that the toll-like receptor 7 and 8 agonist resiquimod (R-848) unlikely affects drug levels of co-administered compounds - Theile, Dirk; Wagner, Lelia; Haefeli, Walter E.; Weiß, Johanna (European journal of pharmaceutical sciences, 2021)
Resiquimod (R-848) is an immune response modifier activating toll-like receptor 7 and 8. Its potential to cause pharmacokinetic interactions with concurrently administered drugs is unknown. To study the time course of the effect of resiquimod in LS180 cells as a model for intestinal tissue, luciferase-based reporter gene assays and reverse transcription polymerase chain reaction were used to investigate whether resiquimod affects the activities of nuclear factor kappa B (NF-ĸB), pregnane x receptor (PXR) or the transcription of selected central genes for drug disposition (cytochrome P-450 isozyme 3A4 (CYP3A4), CYP1A1, UDP-glucuronosyltransferase 1A1 (UGT1A1), ATP-binding cassette transporters ABCC2, ABCB1). Its impact on the activities of organic anion transporting polypeptides 1 or 3 (OATP1B1/3), breast cancer resistance protein (BCRP), P-glycoprotein (P-gp) or CYP3A4 was evaluated using fluorescence- or luminescence-based activity assays. Resiquimod irrelevantly increased NF-ĸB activity after 2 h (1 µM: 1.07-fold, P = 0.0188; 10 µM: 1.09-fold, P = 0.0142), and diminished it after 24 h (1 µM: 0.64-fold, P < 0.0001; 10 µM: 0.68-fold, P < 0.0001) and 30 h (10 µM: 0.68-fold, P = 0.0003). Concurrently, PXR activity after 24 h was marginally increased by 10 µM (1.05-fold, P = 0.0019). Resiquimod did not alter mRNA expression levels, activities of uptake or efflux transporters, or CYP3A4 activity. Given the marginal effects on NF-ĸB, PXR, expression levels of selected PXR target genes, and activities of important drug transporters and CYP3A4 in vitro, resiquimod is not expected to cause major pharmacokinetic drug-drug interactions in vivo.